The significance of colours in Bram Stoker’s Dracula - Jakoša, Nina (Acta neophilologica, 2024)
The article provides a corpus-assisted analysis of colour terms in Bram Stoker’s novel Dracula. The aim of the analysis is to establish whether colours contribute to the novel’s Gothic mood. Colours can be used to evoke specific atmospheres; they also bear symbolic meanings. This makes them a powerful option for enhancing the mood of a Gothic horror novel. The analysis indicates that white, red and black are the most important colours in Dracula, appearing in distinct patterns and contexts.
Keywords: barvna simbolika; colour symbolism; corpus stylistics; Gothic novel; gotski roman; korpusna stilistika; Stoker, Bram